2015
DOI: 10.1097/gme.0000000000000459
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory factor analysis of the Pittsburgh Sleep Quality Index in women with hot flashes

Abstract: Objective Women report poor sleep quality during various stages of the menopause transition and post-menopause, especially those with hot flashes. Sleep measurements vary widely due to the copious instruments available. The Pittsburgh Sleep Quality Index (PSQI) is a frequently used questionnaire that produces a single score for sleep quality. This one-factor structure has not received consistent support in the literature. The goal of this analysis was to determine the best factor structure of the PSQI in women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
(50 reference statements)
4
21
0
Order By: Relevance
“…The factor analysis of the PSQI has been reported on diverse samples including university/college students in Nigeria, India, Chili, Chinese, Ethiopia, Peru and Thailand, pregnant women, community dwelling adults and older adults in America, Australia, China, Ethiopia, Spain, Portugal, Iranian health professionals, adolescents and young adults [ 15 – 17 , 23 , 24 , 26 – 28 , 31 , 34 , 36 , 39 , 41 , 44 , 45 , 52 , 53 , 57 60 ]. Moreover, it has been reported for patient population with breast cancer, Crohn’s disease, depression, diabetes, women with hot flashes, Taiwanese insomniacs, post-traumatic stress disorder, Trauma exposed veterans, temporo-mandibular disorder, traumatic brain injury, fibromyalgia, arthritis, chronic fatigue syndrome, psychiatric disorders and renal transplant patients [ 25 , 27 , 29 , 30 , 32 , 33 , 35 , 37 , 38 , 40 , 42 , 43 , 46 , 49 , 51 , 61 – 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The factor analysis of the PSQI has been reported on diverse samples including university/college students in Nigeria, India, Chili, Chinese, Ethiopia, Peru and Thailand, pregnant women, community dwelling adults and older adults in America, Australia, China, Ethiopia, Spain, Portugal, Iranian health professionals, adolescents and young adults [ 15 – 17 , 23 , 24 , 26 – 28 , 31 , 34 , 36 , 39 , 41 , 44 , 45 , 52 , 53 , 57 60 ]. Moreover, it has been reported for patient population with breast cancer, Crohn’s disease, depression, diabetes, women with hot flashes, Taiwanese insomniacs, post-traumatic stress disorder, Trauma exposed veterans, temporo-mandibular disorder, traumatic brain injury, fibromyalgia, arthritis, chronic fatigue syndrome, psychiatric disorders and renal transplant patients [ 25 , 27 , 29 , 30 , 32 , 33 , 35 , 37 , 38 , 40 , 42 , 43 , 46 , 49 , 51 , 61 – 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…We counted the number of studies reporting any of the following 5 indices: Kaiser-Meyer-Olkin (KMO) Measure of Sampling Adequacy, Bartlett’s sphericity test, determinant score, anti-image, and component correlations (Table 1 ). Eighteen studies reported both the KMO and Bartlett’s sphericity test [ 15 – 17 , 25 , 39 , 43 45 , 51 53 , 57 59 , 61 , 64 , 65 , 67 ], reported inter-item correlations [ 16 , 22 , 24 , 25 , 27 , 29 , 30 , 32 34 , 36 , 37 , 41 , 42 , 45 , 46 , 50 , 53 , 57 , 64 – 67 ], and 11 studies did not report any index [ 23 , 26 , 28 , 31 , 35 , 38 , 40 , 49 , 60 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Studies have documented one, two, and three factor structures for the PSQI, with a three factor model best representing sleep in midlife women with hot flashes. 24 The scale has demonstrated sensitivity to detect changes in sleep during treatment for primary insomnia 25 and sleep problems concurrent with vasomotor symptoms. 5 …”
Section: Methodsmentioning
confidence: 99%